The Influence of Financial Literacy, Lifestyle, and Self-Control on the Financial Management of Students - Luri Lorensa; Ahmad Jibrail (Journal of Educational Management Research, 2025)
This study aims to analyze the influence of financial literacy, lifestyle, and self-control on the financial management of university students. Employing a quantitative, causal-associative design, this study involved a sample of 100 students selected from a population of 764. Data were collected via a validated and reliable questionnaire and analyzed using multiple linear regression after fulfilling all classical assumption tests. The findings reveal that financial literacy, lifestyle, and self-control each have a significant and positive partial effect on students’ financial management. The F-test confirmed that these variables have a significant impact simultaneously, explaining 61.2% of the variance in financial management. Among the three predictors, self-control emerged as the most dominant factor (β = 0.336), highlighting the critical role of psychological discipline. These results underscore the need for a comprehensive approach in higher education, where intervention programs should focus not only on imparting financial knowledge but also on fostering a planned lifestyle and strengthening students’ self-control. The study’s findings emphasize the importance of integrating financial literacy, lifestyle planning, and self-control into higher education curricula.